Effect of the presence of midwife and non-midwife companion on labor pain, duration of delivery, and amount of oxytocin drops in primiparous women: a clinical trial study - Masuomeh Darvishi; Mehdi Ranjbaran; Zinat Jourabchi; Hadi Jafarimanesh (Mashhad University of Medical Sciences, 2019)
Introduction: One of the methods of reducing labor pain is continuous support for pregnant women during labor and delivery. Women's satisfaction from labor experience in terms of care providers, policy-makers of health-care system is considered as one of the important indicators in the quality of mother care. According to controversial results of the studies and lack of evidence which compare the effect of professional and non-professional presence on labor, this study was performed with aim to compare the effect of presence of midwife and non-midwife companion on labor pain, duration of delivery and amount of oxytocin use in primiparous women. Methods: This randomized clinical trial study was performed on 120 primiparous women including three groups of midwives, non-midwife and control group in 2017-2018. The outcome of the study included numerical scale of pain, duration of delivery stages and the amount of oxytocin drops. Data analysis was done using SPSS software (version 20) and Chi-square test, one-way ANOVA and repeated measures analysis of variance. PResults: At the beginning of active phase, pain score in midwife companions group was 2.56 ± 1.83, in non-midwife companions group was 4.03 ± 2.46 and in control group was 4.03 ± 2.46, which showed statistically significant difference (P = 0.014). The effect of time (P <0.001) was significant, but the effect of group (P = 0.386) and the interaction between time and group (P = 0.538) were not statistically significant. According to the results of one-way ANOVA, the least length of delivery in both stages was related to midwife group (P <0.05). Also, midwife companions group had used less oxytocin compared with other groups (P = 0.004).  Conclusion: The presence of a midwife companion beside mothers is a non-invasive and effective intervention in creating physical and mental relaxation during labor and delivery.